Integration of Exogenous Input into a Dynamic Salience Map Revealed by Perturbing Attention - Balan, Puiu F (J Neurosci, 2006)
Although it is widely accepted that exogenous and voluntary factors jointly determine the locus of attention, the rules governing the integration of these factors are poorly understood. We investigated neural responses in the lateral intraparietal area (LIP) to transient, distracting visual perturbations presented during task performance. Monkeys performed a covert search task in which they discriminated the orientation of a target embedded among distractors, and brief visual perturbations were presented at various moments and locations during task performance. LIP neurons responded to perturbations consisting of the appearance of new objects, as well as to abrupt changes in the color, luminance, or position of existing objects. The LIP response correlated with the bottom-up behavioral effects of different perturbation types. In addition, neurons showed two types of top-down modulations. One modulation was a context-specific multiplicative gain that affected perturbation, target, and distractor activity in a spatially nonspecific manner. Gain was higher in blocks of trials in which perturbations directly marked target location than in blocks in which they invariably appeared opposite the target, thus encoding a behavioral context defined by the statistical contingency between target and perturbation location. A second modulation reflected local competitive interactions with search-related activity, resulting in the converse effect: weaker perturbation-evoked responses if perturbations appeared at the location of the target than if they appeared opposite the target. Thus, LIP encodes an abstract dimension of salience, which is shaped by local and global top-down mechanisms. These interacting mechanisms regulate responsiveness to external input as a function of behavioral context and momentary task demands.